2017
DOI: 10.1371/journal.pone.0180196
|View full text |Cite
|
Sign up to set email alerts
|

Clinical assessment and three-dimensional movement analysis: An integrated approach for upper limb evaluation in children with unilateral cerebral palsy

Abstract: IntroductionThe clinical application of upper limb (UL) three-dimensional movement analysis (3DMA) in children with unilateral cerebral palsy (uCP) remains challenging, despite its benefits compared to conventional clinical scales. Moreover, knowledge on UL movement pathology and how this relates to clinical parameters remains scarce. Therefore, we investigated UL kinematics across different manual ability classification system (MACS) levels and explored the relation between clinical and kinematic parameters i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
55
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(64 citation statements)
references
References 34 publications
9
55
0
Order By: Relevance
“…8 These results were reinforced by a recent study of Mailleux et al, 15 which found similar values of correlation between AHA score and the kinematic indices (AVS and APS) in reach-to-grasp vertically, hand-to-mouth, and hand-to-head tasks. In agreement with the clinical impression, a higher relationship could be expected for this degree of freedom.…”
Section: Correlation Between Kinematic Indices Of the Affected Upper mentioning
confidence: 57%
See 4 more Smart Citations
“…8 These results were reinforced by a recent study of Mailleux et al, 15 which found similar values of correlation between AHA score and the kinematic indices (AVS and APS) in reach-to-grasp vertically, hand-to-mouth, and hand-to-head tasks. In agreement with the clinical impression, a higher relationship could be expected for this degree of freedom.…”
Section: Correlation Between Kinematic Indices Of the Affected Upper mentioning
confidence: 57%
“…15 Concurrently, 23 TDC (11 males, 12 females; 22 righthanded, one left-handed; mean age 11y 11mo [SD 2y 5mo]) were included in the study as a control group. 15 Concurrently, 23 TDC (11 males, 12 females; 22 righthanded, one left-handed; mean age 11y 11mo [SD 2y 5mo]) were included in the study as a control group.…”
Section: Participantsmentioning
confidence: 99%
See 3 more Smart Citations